PRPF3-Associated Autosomal Dominant Retinitis Pigmentosa and CYP4V2-Associated Bietti’s Crystalline Corneoretinal Dystrophy Coexist in a Multigenerational Chinese Family - Xiaohong Meng; Qiyou Li; Hong Guo; Haiwei Xu; Shiying Li; Zhengqin Yin (Journal of Ophthalmology)
Purpose. To characterize the clinical and molecular genetic characteristics of a large, multigenerational Chinese family showing different phenotypes. Methods. A pedigree consisted of 56 individuals in 5 generations was recruited. Comprehensive ophthalmic examinations were performed in 16 family members affected. Mutation screening of CYP4V2 was performed by Sanger sequencing. Next-generation sequencing (NGS) was performed to capture and sequence all exons of 47 known retinal dystrophy-associated genes in two affected family members who had no mutations in CYP4V2. The detected variants in NGS were validated by Sanger sequencing in the family members. Results. Two compound heterozygous CYP4V2 mutations (c.802-8_810del17insGC and c.992A>C) were detected in the proband who presented typical clinical features of BCD. One missense mutation (c.1482C>T, p.T494M) in the PRPF3 gene was detected in 9 out of 22 affected family members who manifested classical clinical features of RP. Conclusions. Our results showed that two compound heterozygous CYP4V2 mutations caused BCD, and one missense mutation in PRPF3 was responsible for adRP in this large family. This study suggests that accurate phenotypic diagnosis, molecular diagnosis, and genetic counseling are necessary for patients with hereditary retinal degeneration in some large mutigenerational family.